If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5y + -6)(5y + 6) = 0 Reorder the terms: (-6 + 5y)(5y + 6) = 0 Reorder the terms: (-6 + 5y)(6 + 5y) = 0 Multiply (-6 + 5y) * (6 + 5y) (-6(6 + 5y) + 5y * (6 + 5y)) = 0 ((6 * -6 + 5y * -6) + 5y * (6 + 5y)) = 0 ((-36 + -30y) + 5y * (6 + 5y)) = 0 (-36 + -30y + (6 * 5y + 5y * 5y)) = 0 (-36 + -30y + (30y + 25y2)) = 0 Combine like terms: -30y + 30y = 0 (-36 + 0 + 25y2) = 0 (-36 + 25y2) = 0 Solving -36 + 25y2 = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 25y2 = 0 + 36 Combine like terms: -36 + 36 = 0 0 + 25y2 = 0 + 36 25y2 = 0 + 36 Combine like terms: 0 + 36 = 36 25y2 = 36 Divide each side by '25'. y2 = 1.44 Simplifying y2 = 1.44 Take the square root of each side: y = {-1.2, 1.2}
| (2x+1)(2x-1)= | | x^2+4x+a^2-3a=0 | | 2x(4x^2+3x-5)=y | | 10(t-5)+8=6(3t+3)-11 | | 4x^2+4x+37=0 | | 100000+30Q=150000+20Q | | 10000+30Q=150000 | | 7x^4=448x | | x^3+2x^2-25x+50=0 | | X^2+4xy+4y^2=0 | | 9x-4y=56 | | x+8=2x-6 | | 4x=-3+21 | | 5(x-8)=3(x-6) | | -5.2(2p+4)-1.3(3p-5)= | | 5x+3y=52 | | ln(x)+ln(4)=2 | | 0.33(6x-8)=0.66(5x-2)+9 | | 2y+7x=-10 | | .375x-4=4x | | 2s-13=-31+5s | | 8y-27=-55+y | | 3x^2+12x-3y^2+18y-14=0 | | -7x-7x=-112 | | 4(x+2)=10+3x | | 3x^2+12x-3y^2+18y=14 | | 7x+10x=136 | | -4x-20=-84 | | -4x-20=84 | | x+(x+1)(x+2)=27 | | -82=8+9x | | 9x^2+3=12x |